Linear free energy relationships in the chromium(VI) oxidation of phenols - Gunasekar, Krishnamoorthy (Array, 2009)
Summary:The kinetics of oxidation of phenol by nicotinium dichromate has been studied in 50 % acetic acid-water (v/v) medium. The reaction shows unit order dependence on each, with respect to oxidant and substrate. The reaction is acid catalysed and the medium of low dielectric constant favours the reaction. Increase in ionic strength has negligible effect on the reaction rate. In general, the electron withdrawing substituents enhance the rate of reaction. From the kinetic data obtained, the activation parameters have been calculated and a plausible mechanism has been proposed in accordance with multiparameter correlation analysis